Nanofragmentation of Expanded Polystyrene Under Simulated Environmental Weathering (Thermooxidative Degradation and Hydrodynamic Turbulence) - Mattsson, Karin; Björkroth, Frida; Karlsson, Therese; Hassellöv, Martin (Frontiers in Marine Science, 2021)
Fragmentation of macroplastics into microplastics in the marine environment is probably one of the processes that have generated most drive for developing the microplastics research field. Thus, it is surprising that the level of scientific knowledge on the combinative effect of oxidative degradation and mechanical stressors on fragmentation is relatively limited. Furthermore, it has been hypothesized that plastic fragmentation continues into the nanoplastic size domains, but environmentally realistic studies are lacking. Here the effects of thermooxidative aging and hydrodynamic conditions relevant for the shoreline environment on the fragmentation of expanded polystyrene (EPS) were tested in laboratory simulations. The pre-degraded EPS was cut into pieces and subjected to mechanical, hydrodynamic simulations during four-day stirring experiments. Subsamples were filtered and subsequently analyzed with light microscopy with automated image analysis particle size distribution determinations, polymer identification with Raman spectroscopy, Scanning Electron Microscopy (SEM) with automated image analysis particle size distribution. The nanoplastic size fraction was measured using nanoparticle tracking analysis. In addition, the degree of polymer oxidation was spectroscopically characterized with Fourier transform infrared (FTIR) spectroscopy. The results illustrate that fragmentation of the mesoplastic objects is observed already after 2 days, but that is more distinct after 4 days, with higher abundances for the smaller size fractions, which imply more release of smaller sizes or fragmentation in several steps. For the nanoplastic fraction, day four shows a higher abundance of released or fragmented particles than day two. The conclusions are that nanofragmentation is an important and understudied process and that standardized test protocols for both thermooxidative degradation and mechanical treatments mimicking realistic environmental conditions are needed. Further testing of the most common macro- and mesoplastic materials to assess the rates and fluxes of fragmenting particles to micro- and nanoplastic fractions should be conducted.